Kepribadian dan Kehidupan Hamba Tuhan Menurut 1 Timotius 3:1-13 - Bernike Sihombing (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2014)
The author explains about the characteristic servant of God, a practical discussion with analyzing the 1 Timothy 3:1-13. This text is the key to understand the various aspects characteristic servant of God, in order to have a good character according to the standard of the God